From Qitāl to Difā’: The Meaning and Behavior of Jihad according to Jihadists in Semarang City - Anthin Lathifah (Al-Ahkam, 2018)
This paper describes the meaning and act of religion-based jihad according to some jihadists in Semarang city. Insisting that the real meaning of Jihad is qitāl (war, to fight) as said by the verse “La hukma Illa lillah” and hadith “faqtulū haythu wajadtumūhum” they, however, still propose another jihad called difā’ (defensive, to survive) for people who cannot meet the requirement of qitāl. The different act of jihad emerges because of its different factors behind such as social, economy, politics, psychology and others. The shift from qitāl to difā’ takes place by the process of humanizing the jihadists using: 1) personal approach by their morally closest men; 2) basic need approach such as economy, existency and peace; 3) religious approach by understanding that what they do is to fully adhere to Islam (kaffah); 4) emotional approach by caring and giving them empathy; 5) social approach by building solidarity to help their comrades.[]Artikel ini mendeskripsikan makna dan perilaku jihad dari para pelaku jihad berbasis agama di Kota Semarang. Makna jihad yang sebenarnya bagi mereka adalah qitāl sebagaimana ayat “la hukma illa lillah” dan hadits “faqtulū haythu wajadtumūhum”, namun jihad difā’ dapat dilakukan bagi yang tidak memenuhi syarat jihad qitāl. Perbedaan perilaku jihad terjadi karena perbedaan faktor yang melingkupinya, yakni faktor sosial, ekonomi, politik, psikologi dan lainnya. Perubahan perilaku jihad (qitāl) menjadi difā’ terjadi karena proses memanusiakan manusia yang dilakukan dengan: 1) pendekatan personil yang dilakukan oleh orang yang dekat secara moril; 2) pendekatan berbasis kebutuhan primer mereka baik ekonomi, eksistensi ataupun rasa aman; 3) pendekatan agama dilakukan dengan memahami apa yang mereka lakukan adalah dalam rangka melakukan Islam secara kaffah; 4) pendekatan emosional dengan memberi perhatian atau empati; 5) pendekatan sosial dengan membangun solidaritas untuk membantu teman-teman seperjuangannya.